Preparation method for preparing lithium ion battery positive electrode material through secondary sintering
Through secondary sintering technology, combined with graphene oxide, hydroxylated carbon nanotubes and modified silane coupling agent, an N-doped carbon layer is formed, which solves the problem of poor circulation performance of the positive electrode material of lithium-ion batteries and significantly improves the battery's Discharge capacity and cycle stability extend battery life and simplify production processes.
Patent Information
- Application Number
- CN202411592374.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2024-12-31
AI Technical Summary
The positive electrode material of lithium-ion batteries prepared in the prior art has poor circulation performance, resulting in short battery life.
By using the secondary sintering preparation method, by mixing nickel-cobalt manganese hydroxide, graphene oxide, hydroxylated carbon nanotubes and modified silane coupling agent in aqueous ethanol, forming a coating liquid and performing two sintering products with the primary sintering product. Sub-sintering, a conductive network with an N-doped carbon layer is formed, which improves the transmission efficiency of lithium ions and the cycling stability of the battery.
It improves the crystal structure stability of the positive electrode material of lithium-ion battery, reduces the residual alkali content on the surface, improves the discharge capacity and cycle stability, extends the cycle life of the battery, and simplifies the process flow to facilitate large-scale production.
Smart Images

Figure BDA0005125923760000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a positive electrode material for a lithium ion battery by secondary sintering. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles, hybrid vehicles and energy storage systems due to their high capacity and high energy density. As one of the core components of lithium-ion batteries, the positive electrode material has a significant impact on the performance of lithium-ion batteries.
[0003] In order to improve the energy density of lithium-ion batteries, high-nickel ternary cathode materials are attracting more and more attention from researchers. High-nickel ternary cathode materials combine LiCoO2, LiNiO2 and LiMn2O4. The presence of Ni is conducive to increasing the amount of reversible lithium embedded in the material; the presence of Co helps to reduce cation mixed discharge, reduce impedance value, increase conductivity and improve cycle performance; Mn not only reduces material cost, but also improves material stability and safety.
[0004] Patent announcement number CN107994212B discloses a lithium-ion battery layered positive electrode material and a preparation method thereof. The patent uniformly mixes nickel-cobalt-manganese hydroxide, lithium source and nano-oxide additives, and obtains unmodified powder by first sintering; the unmodified powder is stirred with water, centrifuged to obtain solid matter, dried, and crushed to obtain washed powder; lithium bis(oxalate)borate is dissolved in an organic solvent, and then the washed powder is added and mixed, followed by stirring and evaporation, and then sintered for the second time to obtain a lithium-ion battery layered positive electrode material. However, the lithium battery positive electrode material prepared by the patent and the prior art still has the problem of poor cycle performance. Summary of the invention
[0005] In order to solve the problem that the positive electrode material of a lithium battery prepared by the prior art still has poor cycle performance, the purpose of the present invention is to provide a method for preparing a positive electrode material of a lithium ion battery by secondary sintering.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a positive electrode material for a lithium-ion battery by secondary sintering comprises the following steps:
[0008] S1, uniformly mixing nickel-cobalt-manganese hydroxide, lithium hydroxide and nano-oxide additives, and performing a first sintering to obtain a primary sintering product;
[0009] S2. Adding graphene oxide, hydroxylated carbon nanotubes and modified silane coupling agent into an ethanol aqueous solution with a volume fraction of 90%, stirring for 1-2 hours, and obtaining a coating solution; the modified silane coupling agent contains a phosphoric acid group and a triazole ring.
[0010] The usage ratio of graphene oxide, hydroxylated carbon nanotubes, modified silane coupling agent and ethanol aqueous solution is 2-4 g: 1.5-2.5 g: 0.02-0.06 g: 100 mL.
[0011] S3, mixing the coating liquid with the primary sintering product, and obtaining a positive electrode material for a lithium-ion battery through secondary sintering.
[0012] The dosage ratio of the coating liquid to the primary sintering product is 40-45 mL: 50 g.
[0013] Graphene has excellent mechanical properties, thermal properties and electrical conductivity, and is widely used in mobile devices, aerospace and new energy battery fields. Carbon nanotubes have excellent electrical conductivity and a large specific surface area, and can be directly applied to lithium-ion batteries. Its special tubular structure and intertwined network structure can accelerate the Li + The transmission rate of carbon nanotubes is high, and carbon nanotubes themselves have a certain conductive capacity. Graphene oxide and hydroxylated carbon nanotubes are made into a coating solution. Carbon nanotubes can serve as a scaffold to support layered graphene to form a three-dimensional conductive network with many pore structures, but graphene oxide and hydroxylated carbon nanotubes are easy to agglomerate, thus affecting the formation of the conductive network.
[0014] Adding modified silane coupling agents to graphene oxide and hydroxylated carbon nanotubes can effectively improve the agglomeration of graphene oxide and hydroxylated carbon nanotubes in the solution, forming a more uniform dispersion system, which is conducive to the formation of a conductive network, providing a more efficient transmission path for the transmission of lithium ions, and improving the charge and discharge specific capacity of lithium-ion battery positive electrode materials. In addition, the coating of the coating liquid effectively prevents the corrosion of the positive electrode material by the electrolyte byproducts, protects the structure of the positive electrode material, and improves the cyclability of the positive electrode material of the lithium-ion battery.
[0015] The modified silane coupling agent contains phosphate groups and triazole rings. Before the secondary sintering, some residual alkali will remain on the surface of the primary sintering product. The presence of the surface residual alkali will change the surface charge distribution of the positive electrode material, resulting in accelerated capacity decay of the electrode during the cycle, thereby reducing the cycle performance of the battery. The coating solution containing phosphate groups can react with the residual alkali on the surface of the primary sintering product, thereby reducing the content of residual alkali on the surface of the primary sintering product, reducing the side reactions between the electrolyte and the inside of the particles, improving the cycle retention rate, and extending the battery life; the triazole ring contains rich nitrogen elements. This special N-containing carbon source can form an in-situ N-doped carbon layer during the calcination process. N doping can introduce additional electrons or holes in the lattice of the carbon material, thereby changing its electronic structure. This change makes the N-doped carbon layer have a higher electron mobility, thereby improving the conductivity of the material, making the transmission of electrons in the positive electrode material smoother, thereby increasing the discharge capacity of the battery; the N-doped carbon layer reduces the energy barrier for ion penetration, making it easier for lithium ions to migrate during the battery cycle, thereby reducing the polarization phenomenon and capacity attenuation of the battery and extending the cycle life of the battery. Furthermore, the N-doped carbon layer can also serve as a protective layer to reduce the side reactions between the electrolyte and the positive electrode material, further extending the cycle life of the battery.
[0016] Furthermore, in step S1, the chemical formula of the primary sintering product is Li x (Ni a Co b Mn c ) 1-y M y O2, 0.96≤x≤1.04, 0.01≤y≤0.06, 0.8≤a≤0.9, a+b+c=1, M is at least one of Al element, Mg element, Ti element and Zr element.
[0017] Furthermore, in step S1, the nano-oxide additive is at least one of nano-oxides of Al, Mg, Ti and Zr.
[0018] Furthermore, in step S1, the molar ratio of Li ions to nickel-cobalt-manganese hydroxide is 1.01-1.05:1, and the molar ratio of the nano-oxide additive to nickel-cobalt-manganese hydroxide is 0.01-0.06:1.
[0019] Furthermore, in step S1, the atmosphere of the first sintering is pure oxygen, the temperature of the first sintering is 700-800° C., and the time of the first sintering is 8-20 hours.
[0020] Furthermore, in step S3, the atmosphere of the second sintering is argon, the sintering temperature is 450-500° C., and the sintering time is 2-4 hours.
[0021] Furthermore, the preparation method of the modified silane coupling agent is:
[0022] A1: Add 12-azidododecylphosphoric acid, chloropropyne, ascorbic acid and copper sulfate to a 50% methanol aqueous solution, react at 20-30° C. for 5-12 hours, wash and dry to obtain a triazole compound;
[0023] The dosage ratio of 12-azidododecylphosphoric acid, chloropropyne, ascorbic acid, copper sulfate and 50% methanol aqueous solution is 29.1 g: 8.2 g: 1-2 g: 0.8-1.6 g: 400-500 L.
[0024] The azide group of 12-azidododecylphosphoric acid and the carbon-carbon triple bond of chloropropyne undergo an azide-alkynyl cycloaddition reaction to generate a triazole ring, and ascorbic acid and copper sulfate are used as catalysts to catalyze the reaction.
[0025] A2: Mix 3-aminopropyltriethoxysilane, triethylamine and anhydrous ethanol, stir at -40°C for 10 minutes, then add the triazole compound, stir at -40°C for 15-20 minutes, remove, stir at room temperature for 2.5-3 hours, filter and dry to obtain a modified silane coupling agent.
[0026] The usage ratio of 3-aminopropyltriethoxysilane, triethylamine, anhydrous ethanol and triazole compound is 22.1 g: 20 mL: 600-700 L: 33.8 g.
[0027] The -Cl in the triazole compound reacts with the amino group in 3-aminopropyltriethoxysilane to generate aniline, thus obtaining a modified silane coupling agent.
[0028] Beneficial effects of the present invention:
[0029] 1. The lithium-ion battery positive electrode material obtained by the present invention has a stable crystal structure, low surface residual alkali content, high discharge capacity and good cycle stability. The process flow of the present invention is simple and easy to mass produce.
[0030] 2. The present invention is conducive to the preparation of lithium manganese iron phosphate positive electrode materials with the best comprehensive performance by accurately controlling the amount of coating liquid added. When the amount of coating liquid added is too much, the excessive coating liquid is easy to accumulate, hindering the transmission of lithium ions and reducing the discharge specific capacity of the positive electrode material; when the coating liquid is too little, it cannot completely cover the surface of the positive electrode material, resulting in incomplete coating. This will cause part of the surface of the positive electrode material to be directly exposed to the electrolyte, increasing the risk of side reactions between the electrolyte and the positive electrode material, and reducing the cycle stability of the positive electrode material. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The graphene oxide in the present invention was purchased from Hangzhou Gaoxin Technology Co., Ltd. (Hangzhou, China); the hydroxylated carbon nanotubes were H792174 hydroxylated multi-walled carbon nanotubes purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 308068-56-6.
[0033] Preparation Example 1
[0034] The preparation method of the modified silane coupling agent of this preparation example is:
[0035] A1: Add 29.1 g of 12-azidododecylphosphoric acid, 8.2 g of chloropropyne, 1 g of ascorbic acid, and 0.8 g of copper sulfate to 400 L of 50% methanol aqueous solution, react at 20° C. for 5 h, wash, and dry to obtain a triazole compound;
[0036] A2: Using anhydrous and oxygen-free operation technology (SchlenK), the SchlenK bottle was closed and nitrogen was exchanged three times, then protected with nitrogen and placed in a low-temperature tank at -40°C, 22.1g of 3-aminopropyltriethoxysilane, 20mL of triethylamine, and 700L of anhydrous ethanol were added to the SchlenK bottle, and 33.8g of triazole compound was added after stirring at -40°C for 10min. After stirring at -40°C for 15min, the mixture was removed and stirred at room temperature for 2.5h. The mixture was filtered and dried to obtain a modified silane coupling agent.
[0037] Preparation Example 2
[0038] The preparation method of the modified silane coupling agent of this preparation example is:
[0039] A1: Add 29.1 g of 12-azidododecylphosphoric acid, 8.2 g of chloropropyne, 2 g of ascorbic acid, and 1.6 g of copper sulfate to 500 L of 50% methanol aqueous solution, react at 20-30° C. for 12 h, wash, and dry to obtain a triazole compound;
[0040] A2: Using anhydrous and oxygen-free operation technology (SchlenK), the SchlenK bottle was closed and nitrogen was exchanged three times, then protected with nitrogen and placed in a -40°C low-temperature tank, 22.1 g of 3-aminopropyltriethoxysilane, 20 mL of triethylamine, and 650 L of anhydrous ethanol were added to the SchlenK bottle, and 33.8 g of triazole compound was added after stirring at -40°C for 10 min. After stirring at -40°C for 20 min, the mixture was removed and stirred at room temperature for 3 h. The mixture was filtered and dried to obtain a modified silane coupling agent.
[0041] Preparation Example 3
[0042] The preparation method of the modified silane coupling agent of this preparation example is:
[0043] A1: 8.7 g of 2-azidoethanol, 8.2 g of chloropropyne, 1 g of ascorbic acid, and 0.8 g of copper sulfate were added to 450 L of 50% methanol aqueous solution, reacted at 20° C. for 5 h, washed, and dried to obtain a triazole compound;
[0044] A2: Using anhydrous and oxygen-free operation technology (SchlenK), the SchlenK bottle was closed and nitrogen was exchanged three times, then protected with nitrogen and placed in a -40°C low-temperature tank, 22.1 g of 3-aminopropyltriethoxysilane, 20 mL of triethylamine, and 600 L of anhydrous ethanol were added to the SchlenK bottle, and 33.8 g of triazole compound was added after stirring at -40°C for 10 min. After stirring at -40°C for 15 min, the mixture was removed and stirred at room temperature for 2.5 h. The mixture was filtered and dried to obtain a modified silane coupling agent.
[0045] Preparation Example 4
[0046] The silane coupling agent used in this preparation example is 3-aminopropyltriethoxysilane.
[0047] Example 1
[0048] This embodiment provides a method for preparing a positive electrode material for a lithium ion battery by secondary sintering, comprising the following steps:
[0049] S1. Ni 0.9 Co 0.06 Mn 0.04 (OH)2, lithium hydroxide and nano-alumina additives are mixed evenly, and Li ions and Ni 0.9 Co 0.06 Mn 0.04 The molar ratio of (OH)2 is 1.01:1; nano-alumina and Ni 0.9 Co 0.06 Mn 0.04 The molar ratio of (OH)2 is 0.01:1, and the sintering is carried out at 700°C for 8 hours in a pure oxygen atmosphere to obtain a primary sintering product;
[0050] S2, adding 2 g of graphene oxide, 1.5 g of hydroxylated carbon nanotubes, and 0.02 g of the modified silane coupling agent prepared in Preparation Example 1 to 100 mL of 90% ethanol aqueous solution, stirring for 1 h to obtain a coating solution;
[0051] S3. Mix 40 mL of the coating liquid with 50 g of the primary sintering product, and sinter at 450-500° C. for 2 h under an argon atmosphere to obtain a positive electrode material for a lithium-ion battery.
[0052] Example 2
[0053] This embodiment provides a method for preparing a positive electrode material for a lithium ion battery by secondary sintering, comprising the following steps:
[0054] S1. Ni 0.85 Co 0.1 Mn 0.05 (OH)2, lithium hydroxide and nano-alumina additives are mixed evenly, and Li ions and Ni 0.85 Co 0.1 Mn 0.05 The molar ratio of (OH)2 is 1.03:1; nano-alumina and Ni 0.85 Co 0.1 Mn 0.05 The molar ratio of (OH)2 is 0.03:1, and the sintering is carried out at 750℃ for 14h in a pure oxygen atmosphere to obtain a primary sintering product;
[0055] S2, adding 3 g of graphene oxide, 2 g of hydroxylated carbon nanotubes, and 0.04 g of the modified silane coupling agent prepared in Preparation Example 2 to 100 mL of 90% ethanol aqueous solution, stirring for 1.5 h to obtain a coating solution;
[0056] S3. Mix 43 mL of the coating liquid with 50 g of the primary sintering product, and sinter at 475° C. for 3 h under an argon atmosphere to obtain a positive electrode material for a lithium-ion battery.
[0057] Example 3
[0058] This embodiment provides a method for preparing a positive electrode material for a lithium ion battery by secondary sintering, comprising the following steps:
[0059] S1. Ni 0.8 Co 0.1 Mn 0.1 (OH)2, lithium hydroxide and nano-alumina additives are mixed evenly, and Li ions and Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of (OH)2 is 1.05:1; nano-alumina and Ni0.8 Co 0.1 Mn 0.1 The molar ratio of (OH)2 is 0.06:1, and the sintering is carried out at 800°C for 20 hours in a pure oxygen atmosphere to obtain a primary sintering product;
[0060] S2, adding 4 g of graphene oxide, 2.5 g of hydroxylated carbon nanotubes, and 0.06 g of the modified silane coupling agent prepared in Preparation Example 2 to 100 mL of 90% by volume ethanol aqueous solution, stirring for 2 h to obtain a coating solution;
[0061] S3. Mix 45 mL of the coating liquid with 50 g of the primary sintering product, and sinter at 500° C. for 4 h under an argon atmosphere to obtain a positive electrode material for a lithium-ion battery.
[0062] Comparative Example 1
[0063] A method for preparing a positive electrode material for a lithium-ion battery by secondary sintering, compared with Example 1, is different in that the modified silane coupling agent in step S2 of Example 1 is replaced by the product prepared in Preparation Example 3, and the remaining raw materials, processes and parameters are the same as Example 1.
[0064] Comparative Example 2
[0065] A method for preparing a positive electrode material for a lithium-ion battery by secondary sintering, compared with Example 1, is different in that the modified silane coupling agent in step S2 of Example 1 is replaced by the product prepared in Preparation Example 4, and the remaining raw materials, processes and parameters are the same as Example 1.
[0066] Comparative Example 3
[0067] A method for preparing a positive electrode material for a lithium-ion battery by secondary sintering, compared with Example 1, is different in that the modified silane coupling agent in step S2 of Example 1 is removed, and the remaining raw materials, processes and parameters are the same as Example 1.
[0068] Comparative Example 4
[0069] A method for preparing a positive electrode material for a lithium-ion battery by secondary sintering. Compared with Example 1, the difference is that the "40 mL coating solution" in Example 1 is replaced by "35 mL coating solution", and the remaining raw materials, processes and parameters are the same as Example 1.
[0070] Comparative Example 5
[0071] A method for preparing a positive electrode material for a lithium-ion battery by secondary sintering, compared with Example 3, the difference is that the "45mL coating solution" in Example 3 is replaced by "50mL coating solution", and the remaining raw materials, processes and parameters are the same as Example 3.
[0072] The positive electrode materials of lithium batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were respectively used to uniformly mix the positive electrode materials, carbon black conductive agent, binder PVDF and NMP in a weight ratio of 95:2.5:2.5:5 to prepare the positive electrode slurry of the battery. The slurry was coated on an aluminum foil with a thickness of 20-25um, vacuum dried and rolled to form a positive electrode sheet, with a lithium metal sheet as the negative electrode, and an electrolyte prepared by dissolving 1.5 mol of lithium hexafluorophosphate in 1L of a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC), wherein the volume ratio of EC and DMC in the mixed solvent was 1:1, and button batteries were assembled.
[0073] The electrical performance test of the material was carried out at 25°C using a blue battery test system with a test voltage range of 3V-4.5V; the first charge and discharge specific capacity and 50-week capacity retention rate were tested. The test results are shown in Table 1.
[0074] Table 1
[0075]
[0076] It can be seen from the above data that the lithium battery positive electrode materials prepared in Examples 1-3 have excellent electrochemical properties. The coating solution of Comparative Example 1 does not contain a phosphate group, so it cannot react with the residual alkali on the surface of the primary sintering product, and the specific capacity and cycle efficiency of the battery are low; the coating solution of Comparative Example 2 does not contain a phosphate group and a triazole ring, and thus cannot form an N-doped carbon layer, and the specific capacity and cycle efficiency of the battery are low; no coupling agent is added in Comparative Example 3, the dispersion of graphene oxide and hydroxylated carbon nanotubes in the coating solution is poor, and there are no other functional groups, so the specific capacity and cycle efficiency of the battery are lower than those of Comparative Example 1 and Comparative Example 2; the coating solution content in Comparative Example 4 is less, and the comprehensive performance of the material is reduced; the coating solution in Comparative Example 5 is too much, and the comprehensive performance of the material is also reduced compared to Example 3.
[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a positive electrode material for a lithium-ion battery by secondary sintering, characterized in that: The following steps are involved: S1, uniformly mixing nickel-cobalt-manganese hydroxide, lithium hydroxide and nano-oxide additives, and performing a first sintering to obtain a primary sintering product; S2, adding graphene oxide, hydroxylated carbon nanotubes, and a modified silane coupling agent into an ethanol aqueous solution with a volume fraction of 90%, stirring for 1-2 hours to obtain a coating solution; the modified silane coupling agent contains a phosphoric acid group and a triazole ring; S3, mixing the coating liquid with the primary sintering product, and obtaining a positive electrode material for a lithium-ion battery through secondary sintering.
2. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 1, characterized in that: In step S1, the chemical formula of the primary sintering product is Li x (Ni a Co b Mn c ) 1-y M y O2, 0.96≤x≤1.04, 0.01≤y≤0.06, 0.8≤a≤0.9, a+b+c=1, M is at least one of Al, Mg, Ti and Zr; the nano-oxide additive is at least one of the nano-oxides of Al, Mg, Ti and Zr.
3. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 1, characterized in that: In step S1, the molar ratio of Li ions to nickel-cobalt-manganese hydroxide is 1.01-1.05:1, and the molar ratio of the nano-oxide additive to nickel-cobalt-manganese hydroxide is 0.01-0.06:
1.
4. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 1, characterized in that: In step S1, the first sintering atmosphere is pure oxygen, the temperature is 700-800°C, and the time is 8-20h.
5. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 1, characterized in that: In step S2, the usage ratio of graphene oxide, hydroxylated carbon nanotubes, modified silane coupling agent and ethanol aqueous solution is 2-4 g: 1.5-2.5 g: 0.02-0.06 g: 500 mL.
6. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 1, characterized in that: In step S3, the ratio of the coating liquid to the primary sintering product is 40-45 mL:50 g.
7. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 1, characterized in that: In step S3, the atmosphere of the second sintering is argon, the sintering temperature is 450-500° C., and the sintering time is 2-4 hours.
8. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 1, characterized in that: The preparation method of the modified silane coupling agent is: A1: Add 12-azidododecylphosphoric acid, chloropropyne, ascorbic acid and copper sulfate to a 50% methanol aqueous solution, react at 20-30° C. for 5-12 hours, wash and dry to obtain a triazole compound; A2: Mix 3-aminopropyltriethoxysilane, triethylamine and anhydrous ethanol, stir at -40°C for 10 minutes, then add the triazole compound, stir at -40°C for 15-20 minutes, remove, stir at room temperature for 2.5-3 hours, filter and dry to obtain a modified silane coupling agent.
9. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 8, characterized in that: In step A1, the usage ratio of 12-azidododecylphosphoric acid, chloropropyne, ascorbic acid, copper sulfate, and 50% methanol aqueous solution is 29.1 g: 8.2 g: 1-2 g: 0.8-1.6 g: 400-500 L.
10. The method for preparing a positive electrode material for a lithium-ion battery by secondary sintering according to claim 8, characterized in that: In step A2, the usage ratio of 3-aminopropyltriethoxysilane, triethylamine, anhydrous ethanol and triazole compound is 22.1 g: 20 mL: 600-700 L: 33.8 g.
Citation Information
Patent Citations
A layered cathode material for lithium-ion batteries and its preparation method
CN107994212B
